High performance polydimethylsiloxane pervaporative membranes with hyperbranched polysiloxane as a crosslinker for separation of n-butanol from water1. Issue 65 (16th July 2015) - Bai, Yunxiang; Dong, Liangliang; Lin, Jiaqiang; Zhu, Yuanhua; Zhang, Chunfang; Gu, Jin; Sun, Yuping; Xu, Youyi
<x xml:space="preserve">Abstract</x> Novel hyperbranched polysiloxane crosslinkers, HPSiO, were synthesized to prepare high performance polydimethylsiloxane pervaporation membranes HPSiO-c-PDMS membranes for recovering n-butanol from aqueous solution by pervaporation.